Tell us no secrets: St. Irenaeus’ contra-gnostic doctrine of communion - Springer, Don W. (Vox Patrum, 2018)
Discussion related to the potential for mystical union with God was largely absent from the writings of the Church Fathers prior to the late-second century. Toward the end of that century, however, the concept of communion with God emerged as a topic of interest in both early Christian and Gnostic literature. St. Irenaeus of Lyons was among the earliest Christian writers to critically reflect on the subject. He argued that participation with the divine was possible only in the “orthodox” churches and required three key elements: a life lived in connection to the Spirit of God, in community with the true people of God, while bearing evidence of godly piety and virtue. Whereas Gnostic conceptions of communion frequently included an emphasis on the reception of an exclusive, secret gnosis, Irenaeus’ paradigm offered a public, progressive path of ascent to God.